(untitled) (Journal of Informatics and Mathematical Sciences, 2025)
Job sequencing refers to the process of determining the most suitable order for performing a number of different jobs across a limited number of available resources, services or facilities to make effective use of these available facilities and achieve greater output with minimum time delay. This study introduces an innovative heuristic technique called the Time Deviation Technique. This technique helps in obtaining the optimal job schedule and also minimizes the total elapsed time and idle time. Here we first apply the new method to the n-jobs, 2 machines problem and extend it to the n-jobs, 3 machines problem. And lastly, we applied this method to the n-jobs, m-machines problem after converting into 2 machines n jobs problems by using the condition of Johnson’s method. The proposed technique is very simple and easy to understand. For this we have given examples numerical illustration of job sequencing problem of n jobs 2 machines, n jobs 3 machines and n jobs m machines problem.